Dampak Marketplace Layout Design, Sales Promotion dan Customer Review Terhadap Impulse Buying - Isalman, Isalman; Putera, Asrip (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
The Shopee marketplace continues to show its existence as the marketplace with the most visitors. The distinctive color combination and well-arranged navigation menu can provide a different feel when visiting the maketplace. Information about various products can be seen very clearly on the main homepage, and shopping promo offers are also clearly visible on the slider screen on the main marketplace screen. The marketplace layout is also supported by the existence of a customer review navigation feature as a window for customer reviews of products and services that have been received. Shopee seems to understand how urgent the role of product information and customer reviews is in minimizing risks and supporting unplanned purchasing decisions. Therefore, this research aims to determine the impact of marketplace layout design, sales promotions and customer reviews to increase impulse buying. Research was conducted among Y generation in Kendari City who shopped at the Shopee marketplace. The total sample is 160 respondents. A questionnaire with a Likert scale was used as a data collection tool. Data were analyzed by multiple linear regression using SPSS software. The results of data analysis show that marketplace layout design does not have a significant influence on impulse buying. Meanwhile, sales promotion and customer reviews have a significant positive influence on impulse buying. These findings provide information to marketplace managers and sellers about the urgency of the role of sales promotion as a short-term strategy in accelerating impulse buying. Apart from that, the existence of a customer review feature on the marketplace website can contribute to impulse buying. So it becomes urgent to provide stimulus, such as giving rewards or incentives to customers who have purchased to be able to provide reviews of the products and services they receive.